PENGARUH CITRA MEREK, VARIASI PRODUK DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN PADA ES TEH INDONESIA CABANG BIMA - Sunarsih, Sunarsih; Sri Ernawati (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
Es Teh Indonesia is a Food & Beverages (F&B) company founded by Haidhar Wurjanto in 2018. The purpose of this study was to determine the effect of brand image, product variety and price on purchasing decisions at the bima branch of Indonesian iced tea. The type of research is associative, The research instrument used a questionnaire with a Likert scale. The population used in this study were all consumers of Indonesian iced tea in the Bima branch whose number was unknown (unknown population). The number of samples used in this study were 96 respondents using a purposive sampling technique. Data collection techniques with observation, questionnaires, and literature study. Data analysis techniques by carrying out validity tests, reliability tests, multiple linear regression tests, correlation coefficients, determination tests, t tests, and f tests. The results of this study indicate that brand image and price have a significant effect on purchasing decisions at the Bima branch of Indonesian iced tea and for product variations have no significant effect on purchasing decisions at the Bima branch of Indonesian iced tea.